Age-related retinopathy in NRF2-deficient mice. - Zhenyang Zhao; Yan Chen; Jian Wang; Paul Sternberg; Michael L Freeman; Hans E Grossniklaus; Jiyang Cai (PLoS ONE)
Background Cumulative oxidative damage is implicated in the pathogenesis of age-related macular degeneration (AMD). Nuclear factor erythroid 2-related factor 2 (NRF2) is a transcription factor that plays key roles in retinal antioxidant and detoxification responses. The purposes of this study were to determine whether NRF2-deficient mice would develop AMD-like retinal pathology with aging and to explore the underlying mechanisms. Methods and findings Eyes of both wild type and Nrf2(-/-) mice were examined in vivo by fundus photography and electroretinography (ERG). Structural changes of the outer retina in aged animals were examined by light and electron microscopy, and immunofluorescence labeling. Our results showed that Nrf2(-/-) mice developed age-dependent degenerative pathology in the retinal pigment epithelium (RPE). Drusen-like deposits, accumulation of lipofuscin, spontaneous choroidal neovascularization (CNV) and sub-RPE deposition of inflammatory proteins were present in Nrf2(-/-) mice after 12 months. Accumulation of autophagy-related vacuoles and multivesicular bodies was identified by electron microscopy both within the RPE and in Bruch's membrane of aged Nrf2(-/-) mice. Conclusions Our data suggest that disruption of Nfe2l2 gene increased the vulnerability of outer retina to age-related degeneration. NRF2-deficient mice developed ocular pathology similar to cardinal features of human AMD and deregulated autophagy is likely a mechanistic link between oxidative injury and inflammation. The Nrf2(-/-) mice can provide a novel model for mechanistic and translational research on AMD.